การรักษาสีเขียวของใบไผ่บางชนิด - เล็กโสภี พิชญ์สิชฌ์; เหล็กสูงเนิน นิสา; สังข์แก้ว สราวุธ; ทัดทอง สริน (Thai Journal of Science and Technology, 2020)
This study aimed to study the species, method, and storage time that show the significant potential in green retention for selected bamboo leaves. This will particularly lead to promote the utilization of bamboo leaves for dish decoration. Green color retention techniques for asparagus were applied for the three large-leaf and commonly used bamboo species; i.e. Dendrocalamus asper, Gigantochloa ligulata and G. latifolia. Five treatments were adopted; (1) bare leaves (control), (2) leaves soaked with 0.3 %w/v Mg (OH)2 for 4 min, (3) leaves boiled with 0.5 %w/v MgCO3 for 4 min, (4) leaves boiled with 1 %w/v NaHCO3 for 4 min, and (5) leaves boiled with 0.2 %w/v NH4HCO3 for 4 min. The leaf samples were then subjected to be kept in a vacuum bag at 4 ºC for 30, 60 and 90 days. The results showed that correlation among species, method, and storage time are statistically significant (a ≤ 0.05). The leaves of G. ligulata boiled with 1 %w/v NH4HCO3 for 4 min can retain the green color the most and also can maintain the green color up to 60 days according to CIELAB systems.